CG Technology under the Film Scene Art. Issue 4 (February 2021) - Yang, Lun
Abstract: Since the 21th century, the film had completely entered a digital world. Computer Graphics was involved in all of a filmmaking, give an infinite space to image and is bring more convenient that filmmaking efficient. Film scene is gradually into a virtual age when digital times developing, as an important role in film space. Computer Graphics break the limit of traditional scene-making, and create more complicated scenes design, it pour fresh blood into scene art, expansion the thought of filmmaking and nice process.